Weed Control with Single and Split Herbicide Applications in Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2021)
The objective of the study was to compare season-long weed control from single and sequential herbicide applications in corn. Kochia control was 90% or more late in the season, and did not differ among herbicides. All herbicides except Lumax EZ provided 90% or more Russian thistle control by the season’s end. Palmer amaranth control was lowest when Bicep II Magnum was applied preemergence (PRE) and followed by Lexar EZ postemergence (POST), and when Acuron was applied PRE and again POST. Compared to the untreated control, corn receiving herbicide treatments yielded more than three times as much grain, but yields did not differ among herbicides.
Keywords: sequential applications; residual control; corn herbicide